Correlation Between Anemia And The Incidence Of Low Birth Weight (LBW) - Oktaviana Dewi Lolita; Ira Titisari; Sumy Dwi Antono (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Low Birth Weight (LBW) is newborn who weight less than 2,500 grams. LBW also has an impact on infant namely anemia, hypothermic, hyperbilirubinemia, hypoglyglyemi, respiratory syndrome. One major factor causes anemia during pregnancy. The update of this study is to discuss the relationship between anemia and LBW in developing countries, especially in the continents of Asia and Africa. The purpose of this study is to learn about anemia and LBW in developing countries on the Asian and African continents with literature review. The study design used is the study literature review by scoping study. A journal or article search involves using a keyword or keyword that "anemia to LBW, anemia in pregnancy, Low Birth Weight, LBW" and by using the designated inclusion and exclusion criteria. Assessments of the quality of articles or journals are made by using critical appraisal and will be carried out in 2021. Obtained 11 article publications from 2014 to 2020. From th review result showed that there is a correlation between anemia and low birth weight baby or LBW. The number of anemia in pregnancy does not always determine the number of babies born with LBW. Anemia in pregnancy can be the cause of the LBW baby.